If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 + 2x = -65 Reorder the terms: -10 + 3x + 2x = -65 Combine like terms: 3x + 2x = 5x -10 + 5x = -65 Solving -10 + 5x = -65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5x = -65 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = -65 + 10 5x = -65 + 10 Combine like terms: -65 + 10 = -55 5x = -55 Divide each side by '5'. x = -11 Simplifying x = -11
| t(n)=-6+3(447-1) | | 4(6-9)/6= | | 8-(-4)2-5= | | 5b-b-1=7 | | 2qt=c | | 8x+3y=37 | | 3(t)=67-16t^2 | | p(x)=5x^2-3x+2 | | t(n)=24-5(447) | | 19w-9w-9w+3=20 | | 8x=37-3y | | -3x+3=2x | | (3x+1)(1x+2)= | | 8n=15model | | Xy=126 | | 14n-13n=15 | | 8n=15midel | | 5h+4=34 | | 12/(1/9) | | -2/3(5/6x-3)= | | t(n)=5(447)-3 | | 7/8x=14/40 | | -2/5-7/10= | | 16k+k-14k-2=16 | | 4(1/9) | | -2x^2+2x+17=0 | | 0.02x+0.07(7000-x)=320 | | 3x^2/3-11x^1/2-4=0 | | -2w-5/2=7/5w-6/5 | | y=8x-4x | | x^3+8x^2+22x+20=0 | | 4x-4x+3x-2x=11 |